Imidacloprid Causes DNA Damage in Fish: Clastogenesis as a Mechanism of Genotoxicity - Iturburu, Fernando Gastón (2018)
Neonicotinoids are one of the most widely used insecticides in the world. DNA damage is considered an early biological effect which could lead to reproductive and carcinogenic effects. The present study aimed to evaluate DNA damage and bases oxidation as a mechanism of genotoxicity, on the freshwater fish Australoheros facetus acutely exposed to imidacloprid (IMI). The Comet assay with the nuclease ENDO III enzyme was performed for detecting pyrimidine bases oxidation using blood samples. Micronucleus and other nuclear abnormalities frequencies were also quantified. A significant increase of damage index at 100 and 1000 µg/L IMI was detected; while ENDO III score increased from 1 to 1000 µg/L IMI; varying both in a linear concentration-response manner. MN frequency increased in fish exposed to 1000 µg/L IMI. These results show that short-term exposures to environmentally relevant concentrations of IMI could affect the genetic integrity of fishes through oxidative damage.